Physicochemical and microbiological properties of fermented milk using lactic acid bacteria isolated from dangke - SETIAWAN PUTRA SYAH; ANDI NURUL MUKHLISAH; WENY DWI NINGTIYAS; MUHAMMAD IRFAN; NASRIA ANANDA; ANNISA AMALIA; TASMIN TASMIN (Society for Indonesian Biodiversity, 2024)
Abstract. Syah SP, Mukhlisah AN, Ningtiyas WD, Irfan M, Ananda N, Amalia A, Tasmin. 2024. Physicochemical and microbiological properties of fermented milk using lactic acid bacteria isolated from dangke. Biodiversitas 25: 3876-3883. This study aimed to investigate the effect of milk and starter culture type (commercial and lactic acid bacteria (LAB) isolated from dangke). Two strains of LAB (Lactobacillus fermentum A323L and B111K) and commercial culture were tested for physicochemical and microbiological properties in milk fermentation. The results showed that the type of culture had a significant effect (p<0.05) on pH, titratable acidity, WHC, syneresis, viscosity, and total number of LAB, while the type of milk had a significant effect (p<0.05) on almost all variables, except for protein content and L* (lightness) of fermented milk. Two strains of LAB isolate from dangke produce pH values, titratable acidity, and viscosity that were relatively good compared to commercial cultures and even tended to be better, specifically in terms of the total number of LAB from fermented milk produced. Skimmed milk produced the best-fermented milk in terms of composition, color, pH value, acidity, and viscosity, but was not very good as a medium for LAB growth due to the low number of microbes compared to the other two types, specifically UHT (Ultra High Temperature) low-fat. However, the number of LAB in skimmed milk met the quality standards for fermented milk products. In conclusion, both strains of LAB isolated from dangke could be used as starter cultures in the manufacture of fermented milk with good physicochemical and microbiological properties.